Promoção de saúde através de um curso de capacitação para educação postural junto às professoras da escola municipal Delfim Moreira no município de Guaxupé-MG - Moretti, Maria Júlia Luporini (2009)
The school age represents one of the periods of life where psychological, social, affective and physical occur changes. The physical changes related to the body weight and the stature, are able to cause postural alterations, due to the fast growth to the body experiences that each one has, in the different phases of the life, besides the influence of the hereditary, culture, habits and traumas. In this stage the posture is in a developing process, and the adoption of an incorrect position will have negative repercussion in the future. They estimate that between 65% and 80% of the world-wide population present some disease of the column during life. In Brazil, the National Institute of Social Previdence (INSS) informs that problems related to the column are in the third place of complaints and removals. Some strategies have been used to implant politics of health promotion. In pertaining to school scope one of the components of the health promotion is the education in health with total approach. The present study has the objective of evaluate the health promotion aspects, evaluating and enabling the professors of the 1º to 5º year of the Public school Delfim Moreira, in Guaxupé - City - Brazil.